HUBUNGAN WAKTU TUNGGU PELAYANAN RESEP TERHADAP KEPUASAN PASIEN BPJS DI KLINIK PRATAMA CAHAYA KEBAGUSAN - Kusumawati, Kurnia; Febriansyah, Aji (PHRASE (Pharmaceutical Science) Journal, 2024)
Pharmacy service have a minimum service standard on pharmaceutical service at clinic. To increase pharmacy service at the clinic, an internal quality evaluation is used, namely the waiting time for concocted 60 minutes and ready-made drugs 30 minutes and patient satisfaction. The goals of this research are to (1) analyse patients' perceptions of drug waiting time and (2) identify patients' levels of satisfaction with BPJS, and (3) find out if there is a link between the two. A cross-sectional research approach was used in this study. Using a spearman correlation test and a purposive selection strategy, we were able to collect data from 100 participants. According to the study's findings, 52% of participants reported being very happy with the results, and the average waiting time for ready-made pharmaceuticals was 8 minutes and 50 seconds, while the average waiting time for created drugs was 16 minutes and 14 seconds. Rejecting the null hypothesis, the sig value is 0.048. The results show that the waiting time for prescriptions is within the acceptable range, and that people are generally pleased with the service.Pharmacy service have a minimum service standard on pharmaceutical service at clinic. To increase pharmacy service at the clinic, an internal quality evaluation is used, namely the waiting time for concocted 60 minutes and ready-made drugs 30 minutes and patient satisfaction. The goals of this research are to (1) analyse patients' perceptions of drug waiting time and (2) identify patients' levels of satisfaction with BPJS, and (3) find out if there is a link between the two. A cross-sectional research approach was used in this study. Using a spearman correlation test and a purposive selection strategy, we were able to collect data from 100 participants. According to the study's findings, 52% of participants reported being very happy with the results, and the average waiting time for ready-made pharmaceuticals was 8 minutes and 50 seconds, while the average waiting time for created drugs was 16 minutes and 14 seconds. Rejecting the null hypothesis, the sig value is 0.048. The results show that the waiting time for prescriptions is within the acceptable range, and that people are generally pleased with the service.